Reação de Guerreiro e Machado em portadores de neoplasias malignas - Lopes, Edison Reis (2023)
The authors study the association Chagas, disease-malignant neoplasms in individuais with positive reaction of Machado-Guerreiro. In 23 cases such association has occurred In 21 cases the neoplasm was epithelial in origin; in one case nervous and the last was a melanoma. Based upon these findings and in a previous work, the aa. conclude that it doesn’t seem to exist any inibitor effect on the appearance of neoplasms of epitelial origin, nervous origin or melanomas, in chronic chaga sic individuais.